Comfortable and efficient laundry room design using design thinking and jobs-to-be-done - Sarvia, Elty; Soesilo, Novi; Patricia, Joanna; Augustin, Alena (OPSI, 2025)
Optimal laundry room design is essential for efficiency and comfort in washing, drying and ironing clothes. This research identifies people's need for a functional and comfortable laundry room, along with increasingly busy lifestyles. Non-ergonomic designs can reduce efficiency and comfort. Therefore, this research aims to provide a design solution that suits the preferences of users in Indonesia. A total of  123 respondents participated in the survey, of which 100 met the inclusion criteria through purposive sampling. The design thinking and jobs-to-be-done approaches were applied to explore an in-depth understanding of user needs. The results show that all respondents (100%) agreed that the proposed laundry room design is comfortable, functional, and ergonomically suitable, particularly in the height arrangement of the washing machine, accessibility of the drying area, and ironing layout. Dry room integration was also identified as a significant need. Based on the analysis, the recommended minimum size for an ergonomic laundry room is 220 cm x 300 cm, which supports efficient workflow and user comfort. This study emphasizes the importance of a user centered and ergonomic approach in residential space design to enhance daily comfort and productivity.